ANALISIS KOMUNIKASI PERSUASIF DALAM FILM “MISS SLOANE” (KAJIAN TEKNIK PERSUASIF MENURUT WILLIAM S. HOWELL DAN CHARLES LARSON) - Sartika Sartika (Ensiklopedia of Journal, 2021)
The world of cinema has its own place in the hearts of the people, and is loved by various groups from children to adults. If you look at the storyline of a film, there is an implied message, the film Miss Sloane tells the world of Public Relations (PR) and the twists and turns of drama that a PR person goes through are clearly illustrated in this film. The technique used by Miss Sloane is a study of the realm of persuasive communication. This technique is the approach of William S. Howell and Charles Larson. This study uses a literature or literature method that focuses on references to persuasive communication techniques. The purpose of this research is to find out what persuasive communication techniques are contained in the film.Keywords: Communication, Persuasive, Film